Changes in soil characteristics after six seasons of cereal–legume intercropping in the Southern Pampa - Oelbermann, Maren; Regehr, Alison; Echarte, Laura (Elsevier, 2019)
The Argentine Pampa is one of the most productive agricultural regions in the world, but sole crop management practices have led to soil degradation and losses of soil organic matter. The objective of this study was to evaluate soil organic carbon (SOC) and nitrogen (N) dynamics in 2007 and in 2012 in two intercrop systems [1:2 intercrop (one row of maize (Zea mays L.) and two rows of soybeans (Glycine max L. Merr.)) and 2:3 intercrop (two rows of maize and three rows of soybean)], and in a maize and soybean sole crop. Results showed that C and N input from crop residues was significantly greater (P < 0.05) in the maize sole crop, followed by the intercrops and the soybean sole crop. The land equivalent ratio (LER), based on crop biomass, was significantly greater (P < 0.05) in the 2:3 intercrop. Soil physical and chemical characteristics (bulk density, pH, SOC and N, C/N ratio) were not significantly (P < 0.05) different among treatments and were significantly greater in 2012, except for pH, at all depths. Gross SOC turnover time was significantly longer (P < 0.05) in 2012 compared to 2007 for all treatments and depths, except in the maize sole crop. Soil microbial biomass (SMB) C and N were significantly greater (P < 0.05) in the 2:3 intercrop in both years. To a 40 cm depth, SMB-C turnover time (SMB-CT) was significantly greater (P < 0.05) in the soybean sole crop followed by the intercrops and the maize sole crop in 2007, whereas in 2012, SMB-CT was significantly greater (P < 0.05) in the intercrops followed by the soybean and the maize sole crops. The soil light fraction N (LF-N) was significantly greater (P < 0.05) in the maize sole crop in both years. There was no significant difference (P < 0.05) for LF-C. Our results demonstrated that cereal–legume intercropping is a more sustainable agroecosystem land management practice in the Argentine Pampa, with respect to soil C and N transformations, compared to sole cropping.